Queue Analysis at SPBU Km. 38 And The Impact on Jalan Soekarno Hatta Km. 38 - Ria Enes; Fatmawati Fatmawati; Lilik Damayanti (Civil Engineering Dept, Balikpapan State Polytechnics, 2023)
SPBU KM. 38 is a gas station that distributes subsidized fuel, one of which is diesel. The scarcity and limited availability of fuel, especially diesel fuel, causes many heavy vehicles to queue and cause the traffic loading. This loading has an impact on the performance of the road network around the location, that is Jl. Soekarno Hatta KM. 38. The traffic load due to the diesel queue has a direct impact on the performance of the road network around the location. This study aims to evaluate the service performance of the queuing system and facilities for refueling diesel fuel at SPBU KM. 38 and Knowing the performance of the Jl. Soekarno Hatta KM. 38 based on the MKJI 1997, and the effect of queues for SPBU KM. 38 on road performance. This study uses the Quantitative Research method. Where Quantitative Research has a detailed and measurable characteristic. Based on the results of the study, the highest average time spent waiting in the queue to be served was 0.167 hours≈10.02 minutes. This shows that the facility for refueling diesel fuel is not optimal because the standard time for refueling diesel fuel is 2.5 minutes. The value of the road capacity that has narrowed is 3,072 smp/hour, and the normal road capacity is 3,516 smp/hour. The highest level of service on roads with narrowing occurs on Sundays with service level is D, while on normal roads the highest service levels occur on Mondays and Sundays with service level is C. The queue that occurs causes an increase in the level of service. Therefor it can be concluded that the queue affects the level of service at the research location.